Remarkable efficacy of graft block copolymers as surfactants for reducing interfacial tension. Issue 96 (17th October 2015) - Zhou, Yang; Zhou, Chun; Long, Xinping; Xue, Xianggui; Qian, Wen; Luo, Shikai
<x xml:space="preserve">Abstract</x> This work provides a standard model for experimental applications of graft copolymers as surfactants, especially for reducing the interfacial tension.